COMPARITIVE LEAD UPTAKE AND RESPONSES OF FIVE DIFFERENT PLANT SPECIES GROWN ON LEAD CONTAMINATED SOIL - D. REENA NAVAROJA,; M. KANCHANA, (The Bioscan, 2012)
The present study was focused on identifying the fast growing plants with lead absorbing capacity. The seeds of five different plants species viz., French bean, Cosmos, Marigold, Gomphrena and Soybean were treated with different concentrations of lead nitrate. The concentrations of lead accumulated in the roots by species were: Soybean (6.905ppm), French bean (10.36ppm), Cosmos (6.98ppm), Marigold (3.73ppm) and Gomphrena (4.37ppm). Among the five species evaluated, French bean is the most suitable species for phytoextraction of lead from soil if the root biomass is harvested. On the other hand, Marigold absorbed the smallest amount of lead in its roots.